2022
DOI: 10.1007/s40195-022-01477-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Deformation Behaviors of an Inertia Friction Welded Ti2AlNb Joint: an In-situ Study

Abstract: A defect-free Ti 2 AlNb joint has been obtained by the inertia friction welding (IFW) technology. The weld zone (WZ) is composed of B2 grains refined by discontinuous dynamic recrystallization and enhanced by grain refinement strengthening. And the average microhardness decreases by about 30 HV from the WZ to the base metal. In-situ SEM analysis reveals that the heterogeneous structure of the joint causes strong strain partitioning during tensile deformation. The microcrack initiation occurs at the interface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The results demonstrated that the maximum crystal texture strength in the WNZ was not more than 1.74 times that of the strength in the complete absence of texture. These findings indicated that the preferred orientation of the crystal texture was weak and the microtexture had a negligible effect on the overall texture strength, which confirmed the promiscuous distribution of the crystals displayed in Figure 7 a [ 4 ].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The results demonstrated that the maximum crystal texture strength in the WNZ was not more than 1.74 times that of the strength in the complete absence of texture. These findings indicated that the preferred orientation of the crystal texture was weak and the microtexture had a negligible effect on the overall texture strength, which confirmed the promiscuous distribution of the crystals displayed in Figure 7 a [ 4 ].…”
Section: Resultssupporting
confidence: 67%
“…Therefore, it means FGH96 alloy has excellent comprehensive mechanical properties, as well as excellent corrosion resistance and high-temperature oxidation resistance. It is one of the current superalloys for turbine discs with the highest strength level under operating conditions of 700 °C, and it is the key material for high-performance engine turbine disc rings and other hot components [ 2 , 3 , 4 , 5 ]. Inertia friction welding (IFW) utilizes friction heat generated by the relative motion between the contact surfaces of materials, causing the surfaces of the components intended to be welded and the surrounding material to soften and become rapidly forged.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, constructing the L-J constitutive model of EA4T steel before creating the CA model is very helpful. Many studies have focused on various constitutive models of EA4T steel, [21,25] but an L-J constitutive model of EA4T steel is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive relationship, microstructure, and damage evolution model of EA4T steel during hot deformation have also been investigated. [ 21,22 ] However, a CA model suitable for EA4T steel has not yet been developed. To develop a CA model for EA4T steel, a criterion that can be used to verify the model must be established.…”
Section: Introductionmentioning
confidence: 99%